The law of good people : challenging states' ability to regulate human behavior / Yuval Feldman. - Feldman, Yuval, 1971- (Cambridge University Press, 2018)
Currently, the dominant enforcement paradigm is based on the idea that states deal with 'bad people' - or those pursuing their own self-interests - with laws that exact a price for misbehavior through sanctions and punishment. At the same time, by contrast, behavioral ethics posits that 'good people' are guided by cognitive processes and biases that enable them to bend the laws within the confines of their conscience. In this illuminating book, Yuval Feldman analyzes these paradigms and provides a broad theoretical and empirical comparison of traditional and non-traditional enforcement mechanisms to advance our understanding of how states can better deal with misdeeds committed by normative citizens blinded by cognitive biases regarding their own ethicality. By bridging the gap between new findings of behavioral ethics and traditional methods used to modify behavior, Feldman proposes a 'law of good people' that should be read by scholars and policymakers around the world.